Self-powered high-performance topological crystalline insulators tin selenide/silicon dioxide/silicon heterojunction broadband photodetectors for weak signal detection. Issue 10 (July 2019) - Ling, Cuicui; Guo, Tianchao; Zhao, Lin; Hou, Zhidong; Zhang, Teng
Abstract: Topological crystalline insulators have been demonstrated to possess a broadband absorption spectrum owing to the gapless topological surface states and narrow bulk band gap, which are promising candidates for new generation optoelectronic devices application. Herein, we fabricated a high-quality topological crystalline insulator tin selenide (SnSe)/SiO2 /Si heterostructure using a simple magnetron sputtering method. Our strategy is to build high-quality heterojunctions on silicon wafers by directly growing films to achieve sufficiently large interfacial barriers, enhance the photovoltaic effect of heterojunctions, and make heterojunctions achieve better photo response characteristics. At zero voltage, the current of heterojunction varies from extremely low dark current (∼10 −10 A) to high photocurrent (∼10 −5 A). These advantages make the SnSe/SiO2 /Si heterostructure show a superior photoresponsivity of 39.2 AW −1, an excellent detectivity ( D* ) of 4.2 × 10 16 cmHz 1/2 W −1, a large broadband photoresponse from 365 nm–980 nm and a fast response speed of approximately microseconds. The over-all properties have greatly exceeded those of the reported 2D-based vertical VDW heterojunctions, those 2D film/Si heterojunctions and other Topological insulators/Si heterojunctions photodetectors respecting D*, on-off ratio, bandwidth etc. The SnSe/SiO2 /Si heterojunctions will provide more chance for future optoelectronic devices applications.